Restauraciones estéticas anteriores en piezas con poca estructura remanente: Reporte de un caso - Ferreto, Isabel (Odovtos - International Journal of Dental Sciences, 2011)
This is a case report of a young male who had extensive destruction of both maxillary central incisors and the right lateral incisor. They were restored with DT Light post (BISCO), following manufacturer’s instructions for placement, which includes the use of a fifth generation dentine adhesive OneStep® with their resin cement DUO Link. Later they were restored with porcelains. A great aesthetic results along with restoration of the function was achieved.